(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article comprehensively analyzes the issue of choosing a name for a shopping and service center. Having studied in depth the marketing and psychological aspects of choosing a name, it is argued that a correctly chosen name is one of the important keys to business success. In particular, it is shown that for business entities such as markets, restaurants, beauty salons and training centers, factors such as the impression that the names selected make on the minds of customers, the level of their attraction, the ability to remember and inspire trust are important, and the need to choose reliable, convenient, memorable and simple names is emphasized. In particular, a creative approach, historical and cultural content, compliance with regional (geographical) characteristics and language standards are put forward as the main criteria for choosing a name. Based on the presidential decrees and decrees, the need to take into account national values, traditions and mentality when choosing a name for business entities is highlighted, and choosing a name is a complex process that has risen to the level of art, and in this regard, a semantic analysis of various names is given based on the principles of naming. For example, names such as "Sadaf", "Zarrin", "Fa’zo", "Shaffof", "Sabr" are analyzed, and their lexical and spiritual content is highlighted, how they affect the psychology of the customer. In addition, the article shows how names based on geographical toponyms are firmly established in the memory of customers as an important aspect, and based on observations, the example of the "Kapadokya" and "Sultan Ahmad" restaurants in Fergana shows how the flow of customers increased as a result of the name having an interesting, cultural name. This proves that choosing a name is closely related to the success of the business, marketing strategy and studying customer needs.